2 Sympatho-Vagal Balance Derived from Heart Rate Variability During External and Implantable ECG Monitoring May "Reveal" the Underlying Cause of Blackouts. (31st May 2014) - Anwar, Amir; Allen, Stuart; Virag, Nathalie; Richard Sutton, P; de Mellis, Mirko; Cooper, Paul; Fitzpatrick, Adam
Abstract : Introduction: Blackouts, or "Transient Loss of Consciousness" (TLOC) can be due to syncope, epilepsy or psychogenic causes. Most patients with TLOC are unable to describe their blackout, and often no witness history is available. Cardiac and neurological investigations may be unhelpful. Implantable ECG monitoring with Reveal™ allows symptom/ECG correlation in TLOC, but conventional ECG findings are often non-diagnostic. Hypothesis: Analysis of sympathovagal balance using heart rate variability (HRV) could define distinct "signatures" for syncope, epilepsy and psychogenic disturbance. Methods: 20 patients with TLOC underwent prolonged ECG recording; including cases of reflex syncope, epileptic and non-epileptic seizures, and arrhythmias. Beat-to-beat RR intervals were extracted from the ECG signals. Marginal RR intervals (reflecting cardiac hyper-excitability) were analysed using a statistical assessment of the percentage of RR values outside a confidence interval (window size of 40 beats). Heart rate variability (HRV) was assessed with a parametric spectral estimation using a sliding analysis window of 60–240s, shifted with 5–20s increments. The sympatho-vagal balance was computed as the ratio of the low frequency components (LF: 0.04 Hz–0.15Hz, mainly sympathetic activity) to high frequency components (HF: 0.15–0.4 Hz, parasympathetic activity). Results: Arrhythmia patients (10) showed low marginal intervals (<4%), and changes in HRV (mostly sympathetic) Reflex Syncope patients (Right)(1)showedlow marginal intervals (<4%), and lowering of sympatho-vagal balance before the faint Epileptic Seizure patients (1) showed increased marginality (10–35%) and increased sympatho-vagal balance (10). Non-Epileptic Attack Disorder (NEAD-Left) patients (8), showed high marginal intervals (up to >50%), high sympatho-vagal balance (10–40), high parasympathetic and high sympathetic activity. Events involving an irregular rhythm tend to have high marginality with irregular HRV patterns (high sympathetic and parasympathetic). TLOC due to non-epileptic seizures may show a distinct pattern. Conclusions: The pattern of sympatho-vagal balance derived from the RR variability of the ECG observed during reflex syncope, in tachycardia, and in other arrhythmias is very different from that seen prior to epileptic seizures. Distinct patterns may also help distinguish epilepsy from psychogenic TLOC, but this requires clarification on a larger group of cases. Further work in progress will help define specific sympatho-vagal signatures to help distinguish the causes of TLOC.